Phosphocholine-Specific Antibodies Improve T-Dependent Antibody Responses against OVA Encapsulated into Phosphatidylcholine-Containing Liposomes - Cruz-Leal, Yoelys; López-Requena, Alejandro; Lopetegui-González, Isbel; Machado, Yoan; Alvarez, Carlos; Pérez, Rolando; Lanio, María E. (Frontiers in Immunology, 2016)
Liposomes containing phosphatidylcholine have been widely used as adjuvants. Recently, we demonstrated that B-1 cells produce dipalmitoyl phosphatidylcholine (DPPC)-specific IgM upon immunization of BALB/c mice with DPPC-liposomes encapsulating ovalbumin (OVA). Although this preparation enhanced the OVA-specific humoral response, the contribution of anti-DPPC antibodies to this effect was unclear. Here, we demonstrate that these antibodies are secreted by B-1 cells independently of the presence of OVA in the formulation. We also confirm that these antibodies are specific for phosphocholine. The anti-OVA humoral response was partially restored in B-1 cells-deficient BALB/xid mice by immunization with the liposomes opsonized with the serum total immunoglobulin (Ig) fraction containing anti-phosphocholine antibodies, generated in wild type animals. This result could be related to the increased phagocytosis by peritoneal macrophages of the particles opsonized with the serum total Ig or IgM fractions, both containing anti-phosphocholine antibodies. In conclusion, in the present work it has been demonstrated that phosphocholine-specific antibodies improve T-dependent antibody responses against OVA carried by DPPC-liposomes.